Pengembangan Produk Wirausaha Berbasis Kesehatan dan Wisata untuk Mencetak Wirausaha Muda Berbasis Potensi Lokal - Untung Novianto; Nina Gartika; Riandi Alfin; Debby Nashania; Arsya Arba (Politeknik Piksi Ganesha Indonesia, 2025)
This community service aims to develop local potential through the integration of health-based products and tourism, in order to create young entrepreneurs in partner villages. The focus of community service is directed at processing herbal products that have added value as part of ecotourism and health tourism. The implementation method uses the Participatory Action Research (PAR) approach by actively involving local communities in every stage of the activity, starting from identifying potential, training, production to marketing. This activity has succeeded in empowering 20 participants who are members of the local young entrepreneur group. The results of the community service show an increase in production capacity, understanding of the concept of herbal product branding, and skills in tourism-based digital marketing. This program has an impact on the formation of the identity of local superior products and strengthening the potential of herbal-based tourist villages.